Pengaruh Kemudahan Penggunaan, Manfaat, Dan Risiko Terhadap Minat Penggunaan Qris Untuk Transaksi Pembayaran Pada Umkm Di Pasar Kuliner Gianyar - i komang eris artayasa; I Putu Deddy Samtika; Ni Putu Trisna Windika Pratiwi (Hita Akuntansi dan Keuangan, 2026)
This study aims to examine the influence of perceived ease of use, perceived benefits, and perceived risks on the intention to use QRIS by employing a quantitative approach with a saturated sampling technique involving 83 respondents. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression .The findings reveal that perceived ease of use has a positive and significant effect on the intention to use QRIS, while perceived benefits and perceived risks do not show significant effects, although collectively the three variables have a significant influence with a determination value of 77.7%, indicating that most of the variation in usage intention can be explained by the independent variables. These results highlight that ease of use is the dominant factor driving MSMEs to adopt QRIS, whereas risk is no longer a major concern due to growing trust in the security of digital payment systems.